Perjanjian Gadai Sawah atau Lahan Menurut Perspektif Ekonomi Islam di Lampung Tengah - Nufus, Zakiatun; harini, Nyang Vania Ayuningtyas; Putra, Ungki Prabowo; Mulyana , Nanang (Universitas Muhammadiyah Kotabumi, 2025)
Pawn is a right given to a person who is in debt for a movable or immovable property, such as a car, a car, a rice field, or a house, which is given to him by a debtor or by another person on his behalf. In Varia Agung Village, Seputih Mataram District, Central Lampung Regency, agricultural land pawn agreements are usually made verbally without any agreement on paper between the pawnbroker (rahin) and the pawn recipient (murtahin). In general, the distribution of results between the pawnbroker and the pawn recipient is based only on trust between one another. In the agreement, there are rights and obligations. This research was conducted in Varia Agung Village, Seputih Mataram District, Central Lampung Regency. The population in this study were the pawnbrokers (rahin) and pawn recipients (pawn recipients) in Varia Agung Village, Seputih Mataram District, Central Lampung Regency. The sample in this study was simple random sampling, namely the sampling method was carried out randomly without considering status. The researcher took a sample of 14 consisting of 7 pawners and 7 pawn recipients in Varia Agung Village, Seputih Mataram District, Central Lampung Regency. The data analysis used in this study is qualitative descriptive research, which is a type of research obtained from field studies, then using the field data (interviews) as the main data source. Most farmers practice land pawning due to financial constraints and to finance their children's education. The practice of pawning in Varia Agung Village is more colored by customs which are customs passed down from their predecessors. The practice of land pawning in Varia Agung Village, Seputih Mataram District, Central Lampung Regency is in accordance with the pillars and requirements of pawning according to Islam, but when viewed from the use of collateral, it is not in accordance with the principles of pawning according to Islam, because it gives rise to injustice between al-rahin and al-murtahin.